Kritické posouzení výhodnosti fotovoltaické elektrárny pro rodinný dům - Krejčí, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Předmětem této bakalářské práce je kritické posouzení investičního záměru instalace a potenciálního provozu fotovoltaické elektrárny pro rodinný dům. Zjištění výhodnosti za současného stavu, ve vícero variantách, se zohledněním výhledů růstu cen energií, či nákladů spojení s regulací přenosové soustavy, včetně oportunitních výnosů z potenciálně investované počáteční investice.

The subject of this bachelor thesis is a critical assessment of the investment plan for the installation and potential operation of a photovoltaic power plant for a family house. Determination of the profitability under the current state, in multiple options, taking into account the prospects of energy price increases or costs associated with the regulation of the transmission grid, including the opportunity cost of the potential initial investment.
Critical Assesment of the Benefits of a Photovoltaic Power Plant for a Family House
Keywords: Fotovoltaika; investice; návratnost; oportunitní výnosy; Photovoltaics; investment; payback; opportunity income